Inter-cell interference mitigation using Dynamic Frequency Reuse in LTE-A system - Reza, Asif (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
With the increasing demand for spectrum in communication system Long Term Evolution (LTE) system has been proposed. It allowed the users to use a new and much wider spectrum comparing to the other previous technologies. To utilize the full capacity of the LTE system, Frequency Reuse (FR) concept has been adapted in the communication society. Then further enhancement has been done by using the Orthogonal Frequency Division Multiplexing Access (OFDMA) technique with frequency reuse scheme, it is a promising aspect of transmission of high rate data stream with better system capacity and fading immunity in the modern Long Term Evolution-Advanced (LTE-A) system. Fractional Frequency Reuse (FFR) is the commonly used frequency reuse technique to increase the system capacity. But the problem is, with introduction of FFR, it also increases the Inter Cell Interference (ICI) of the system. The out of cell interference coming from the neighbouring e-NodeBs (eNB) as a result of using the same frequency band and they act as an interference source. This ICI decreases the system capacity, resulting in hampering of communication, browsing and in worst case no connection at all. This condition highly affects the users under a cell specially those who are located in the cell edge areas. In order to take care of this problem an approach called Optimum Power Dynamic Frequency Reuse scheme has been proposed to mitigate the interference thus increasing the system capacity. This scheme use continuous assessment of resource allocation and choosing the best sub-band for the user with least interference. There is a sequential order to be maintained for the users with using off minimum Base station (Bs) transmit power. The cell edge area users are the primary concern in terms of increasing their service quality. MATLAB simulation software has been used to justify the theory that the proposed scheme can increase the capacity of the cell edge areas as well as the cell centre area user. Parameters used for the simulation has been considered for the realistic scenarios. The results achieved from the simulation also indicates that the proposed model can enhance the system capacity by 50% in the cell centre area and 41.8% in the cell edge area comparing to the existing FFR scheme.